2020
DOI: 10.1001/jamanetworkopen.2020.8507
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Videoconference-Based Online Group Intervention for Traumatic Stress in Parents of Children With Life-threatening Illness

Abstract: IMPORTANCE A substantial proportion of parents whose child is diagnosed with a life-threatening illness experience high levels of distress that can lead to long-term mental health difficulties. This can affect the child's recovery. OBJECTIVE To evaluate the efficacy of an acceptance and commitment therapy-based group intervention, delivered using videoconferencing, in reducing posttraumatic stress symptoms (PTSS) in these parents. DESIGN, SETTING, AND PARTICIPANTS This study was a randomized clinical trial of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
59
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(61 citation statements)
references
References 49 publications
0
59
0
2
Order By: Relevance
“…Achieving the right balance between ‘dose’ and ‘burden’ will be key for future studies [ 78 ]. Despite strong evidence that CBT can be helpful for parents [ 15 , 19 , 30 ], it is also possible that CBT was not the ideal therapeutic approach with which to tackle parents’ concerns, with other therapeutic approaches also potentially adding value to parents at this timepoint (e.g., acceptance and commitment therapy [ 22 ]). It is also possible that focusing on only one family member was less efficacious than taking a couples, or family, approach to intervention [ 31 , 79 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Achieving the right balance between ‘dose’ and ‘burden’ will be key for future studies [ 78 ]. Despite strong evidence that CBT can be helpful for parents [ 15 , 19 , 30 ], it is also possible that CBT was not the ideal therapeutic approach with which to tackle parents’ concerns, with other therapeutic approaches also potentially adding value to parents at this timepoint (e.g., acceptance and commitment therapy [ 22 ]). It is also possible that focusing on only one family member was less efficacious than taking a couples, or family, approach to intervention [ 31 , 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given parents’ risk of psychological difficulties, international standards of care state that parents should have early and ongoing access to psychosocial support and evidence-based interventions throughout their child’s cancer trajectory [ 21 ]. Psychological interventions can be effective for parents of children with cancer and other serious illnesses [ 22 , 23 ], yielding small–moderate improvements in QOL, anxiety, and other outcomes [ 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. Cognitive behavior therapy (CBT) interventions that increase parents’ use of adaptive coping strategies may also enhance their parenting skills, reduce parents’ risk of depression/anxiety, and in turn benefit the whole family [ 15 , 19 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, many parents may benefit from provision of informational resources and/or brief psychosocial contact, whereas more specialist psychological interventions may only be indicated for a small subset. Recent studies suggest the delivery of parent informational and support interventions via ehealth technologies, such as telehealth and videoconferencing, shows considerable promise in terms of acceptability and efficacy for parents of children with cancer and other serious medical conditions 44,47–49 . The delivery of online interventions also addresses other barriers to parent participation in psychosocial interventions, such as geographical distance from health services and competing family and child care responsibilities 50 …”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that increasing psychological flexibility through mindfulness therapies reduced maternal depression during the NICU admission and after discharge. 58 ACT interventions can be delivered by a variety of trained facilitators, 24 and demonstrate improved mental health outcomes for parents of children with life-threatening illness, 59 asthma 60 and autism. 61 ACT may be more appropriate for parents in the NICU compared with interventions such as cognitive-behavioural therapy, 24 which demonstrates effectiveness in reducing depression but not anxiety for NICU mothers.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%